Phyto melioration of Irrigated Gray-Earth Meadow Soils - U. Toshbekov; B.N. Xudayberdiyeva (Zien Journals, 2023)
The article discusses the results of an experiment on the cultivation of licorice and its Phyto meliorative effect on the agrophysical and agrochemical properties of gray-meadow saline soils. It has been shown that licorice, used as a phytomeliorant, improves the overall physical properties of the soil and prevents the accumulation of water-soluble salts in the surface layers of the soil by lowering the groundwater level
Keywords: Agrophysical and agrochemical properties; salinity; mineralization